Impact of physical exercise on blood pressure levels in hypertensive patients: A review of recent studies (Research, Society and Development, 2025)
Introduction: Systemic arterial hypertension (SAH) is a chronic disease with high global prevalence and a significant negative impact on public health. Regular physical exercise has been recommended as an effective non-pharmacological strategy for blood pressure control. Objective: To evaluate the influence of physical activity on blood pressure levels in individuals diagnosed with systemic arterial hypertension through a literature review. Methods: A search was conducted in the PubMed, Scielo, and LILACS databases, selecting articles published in the last five years that addressed the relationship between physical exercise and hypertension. Ten studies were included, covering various types of physical activity such as aerobic exercise, resistance training, high-intensity interval training (HIIT), and functional training. Results: The studies indicated that regular physical exercise, especially when performed for periods longer than 10 weeks, leads to significant reductions in both systolic and diastolic blood pressure. Improvements were also observed in blood pressure variability, cardiovascular function, and overall health of hypertensive patients. Combined modalities and positive attitudes toward physical activity enhance these effects. Conclusion: Physical activity is a safe and effective intervention for lowering blood pressure in patients with systemic arterial hypertension and should be incorporated as a key component of the multidisciplinary treatment of this condition.